Effectiveness of Nifurtimox Eflornithine Combination Therapy (NECT) in T. b. gambiense second stage sleeping sickness patients in the Democratic Republic of Congo: Report from a field study - Andrea Kuemmerle (Public Library of Science (PLoS), 2021)
Background Nifurtimox-eflornithine combination therapy (NECT) for the treatment of second stage gambiense human African trypanosomiasis (HAT) was added to the World Health Organization’s Essential Medicines List in 2009 after demonstration of its non-inferior efficacy compared to eflornithine therapy. A study of NECT use in the field showed acceptable safety and high efficacy until hospital discharge in a wide population, including children, pregnant and breastfeeding women, and patients with a HAT treatment history. We present here the effectiveness results after the 24-month follow-up visit. Methodology/Principal findings In a multicenter, open label, single arm phase IIIb study, second stage gambiense HAT patients were treated with NECT in the Democratic Republic of Congo. Clinical cure was defined 24 months after treatment as survival without clinical and/or parasitological signs of HAT. Of the 629 included patients, 619 (98.4%) were discharged alive after treatment and were examined for the presence of trypanosomes, white blood cell count in cerebro-spinal fluid, and disease symptoms. The clinical cure rate of 94.1% was comparable for all subpopulations analyzed at the 24-month follow-up visit. Self-reported adverse events during follow-up were few and concerned mainly nervous system disorders, infections, and gastro-intestinal disorders. Overall, 28 patients (4.3%) died during the course of the trial. The death of 16 of the 18 patients who died during the follow-up period was assessed as unlikely or not related to NECT. Within 24 months, eight patients (1.3%) relapsed and received rescue treatment. Sixteen patients were completely lost to follow-up. Conclusions/Significance NECT treatment administered under field conditions was effective and sufficiently well tolerated, no major concern arose for children or pregnant or breastfeeding women. Patients with a previous HAT treatment history had the same response as those who were naïve. In conclusion, NECT was confirmed as effective and appropriate for use in a broad population, including vulnerable subpopulations. Trial registration The trial is registered at ClinicalTrials.gov, number NCT00906880. Author summary The advanced stage of the neglected tropical disease human African trypanosomiasis was, until relatively recently, treated with an old toxic arsenical drug and there was little investment in an improved treatment option. Eflornithine alone was efficacious, but difficult to administer as it required four two-hour infusions a day for 14 days. Nifurtimox-eflornithine combination therapy (NECT) was developed as a simplified and easier to use treatment and was shown to be effective and sufficiently well tolerated in a randomized clinical trial. The present study was conducted to assess the overall effectiveness, including the feasibility of implementation of NECT under field conditions in a wider population than in the randomized clinical trial. We found that NECT can be implemented under field conditions and in remote areas, with the necessary logistical support and staff training for treatment administration. Adverse events, although very frequent, were considered acceptable given the severity of the disease. Less than 10% of patients showed severe adverse events. Over 24 months, the case fatality rate was 4.5% and relapses were rare (1.3%). The effectiveness of NECT was confirmed in a broad spectrum of second stage gambiense HAT patients, including children, pregnant and breastfeeding women, and patients who had been previously treated for HAT.